Potassium Food sources in Portuguese diet - Nascimento, A.C. (2018)
Potassium is an essential nutrient involved in fluid, acid and electrolyte balance and is required for normal cellular function. Dietary deficiency of potassium is very uncommon due to its widespread occurrence in foods. Potassium is classified as a nutrient of public health concern, because its under consumption has been linked in scientific literature to adverse health outcomes. The aims of this study were to assess the potassium food sources and evaluated the Na/K ratio for the food groups under study. Samples were select according to the Total Diet Study (TDS), including core foods representing the overall diet of a population while covering specific foods containing high levels of chemical substances under review. Foods were collected according to a sampling plan, then were prepared as consumed and pooled before analysis. Analysed samples (111) were grouped according to food classification system FoodEx2 level 1: Composite dishes and soups; meat, eggs and dairy; fish and seafoods, vegetables, legumes and cereals; fruits and confectionery. Analyses were carried out in accordance with ISO standard 17025. Sodium and potassium levels were determined using an Inductively Couple Plasma Atomic Emission Spectrometry–ICP-OES. Sodium and potassium contents ranged from: 8.99-1476 mg/100g in dried figs and lupines and from 7.63-1583 mg/100g in lupines and fresh codfish, respectively. The ratio Na/K presented lower values in fruits in general, dried figs, raisins, unprocessed meat, vegetables and legumes. Higher values of Na/K ratio were found in lupines, ham, sausages, olives, squid, clams and cheese. Lowering the dietary sodium-potassium ratio by increasing the consumption of potassium-rich foods, like fruits in general, legumes and vegetables as shown in our results can be a useful component of dietary advice. Increases in dietary potassium have been shown to delay the incidence of hypertension. Also, potassium-rich foods in general presented lower amounts of sodium.